Educate Children on Early Age Based on the Values of Sunda in Islamic Perspective - Rostika Srihilmawati (International Journal of Emerging Issues in Early Childhood Education, 2022)
The purpose of writing this article is to describe how to educate children based on Sundanese values in an Islamic perspective. The method of explanation is written based on a review of several literature. The result is that to educate children based on Sundanese values in an Islamic perspective is needed thorough understanding That is, in educating children based on the Sundanese-Islamic perspective, it is very much determined by the important role of a mother who must be a role model in educating her sons and daughters, teachers and even the school to make children devoted to Allah and have noble character. Keywords: educating children, Sundanese values, Islamic perspective